Soluble CD40‐ligand (sCD40L, sCD154) plays an immunosuppressive role via regulatory T cell expansion in HIV infection. (October 2014) - Jenabian, M.‐A.; Patel, M.; Kema, I.; Vyboh, K.; Kanagaratham, C.; Radzioch, D.; Thébault, P.; Lapointe, R.; Gilmore, N.; Ancuta, P.; Tremblay, C.; Routy, J.‐P.
Summary CD40/CD40‐ligand (CD40L) signalling is a key stimulatory pathway which triggers the tryptophan (Trp) catabolizing enzyme IDO in dendritic cells and is immunosuppressive in cancer. We reported IDO‐induced Trp catabolism results in a T helper type 17 (Th17)/regulatory T cell (Treg) imbalance, and favours microbial translocation in HIV chronic infection. Here we assessed the link between sCD40L, Tregs and IDO activity in HIV‐infected patients with different clinical outcomes. Plasmatic sCD40L and inflammatory cytokines were assessed in anti‐retroviral therapy (ART)‐naive, ART‐successfully treated (ST), elite controllers (EC) and healthy subjects (HS). Plasma levels of Trp and its metabolite Kynurenine (Kyn) were measured by isotope dilution tandem mass spectrometry and sCD14 was assessed by enzyme‐linked immunosorbent assay (ELISA). IDO‐mRNA expression was quantified by reverse transcription–polymerase chain reaction (RT–PCR). The in‐vitro functional assay of sCD40L on Treg induction and T cell activation were assessed on peripheral blood mononuclear cells (PBMCs) from HS. sCD40L levels in ART‐naive subjects were significantly higher compared to ST and HS, whereas EC showed only a minor increase. In ART‐naive alone, sCD40L was correlated with T cell activation, IDO‐mRNA expression and CD4 T cell depletion but not with viral load. sCD40L was correlated positively with IDO enzymatic activity (Kyn/Trp ratio), Treg frequency, plasma sCD14 and inflammatory soluble factors in all HIV‐infected patients. In‐vitro functional sCD40L stimulation induced Treg expansion and favoured Treg differentiation by reducing central memory and increasing terminal effector Treg proportion. sCD40L also increased T cell activation measured by co‐expression of CD38/human leucocyte antigen D‐related (HLA‐DR). These results indicate that elevated sCD40L induces immunosuppression in HIV infection by mediating IDO‐induced Trp catabolism and Treg expansion.